Adopted Apprentices: Juvenile Recruitment in Australian Circus, 1847–1942. (1st May 2016) - Leon, Mark St
Abstract : Recent studies on the history of circus in Australia draw attention to the practise of recruiting male and female juveniles as trainee performers to augment a circus family or circus troupe. In oral recollections, circus people loosely described these juveniles as "apprenticed" or "adopted." Although several nefarious examples of recruitment have been previously described in detail, historians have not explained the wider contexts in which such recruitment took place. The constant need for circus proprietors to embellish their programs drove the demand for these juveniles. This article explores the factors influencing the supply of juvenile circus labour, focussing on the evolving social, legislative and economic contexts within which juveniles were recruited into circus between 1847 (the foundation year of circus in Australia) and 1942 (when most circus companies temporarily ceased operations owing to wartime restrictions and by which time juvenile recruitment was largely extinguished). The study highlights the worth of deeper scholarly enquiry into this previously neglected group of young workers. It also demonstrates the complexity of labour practises in theatrical entertainments, generally, and in itinerant entertainments such as circus in particular. In doing so, the study suggests the need to reconsider the distinction between the margins and mainstream of Australian labour and social history.